Pemberdayaan Perempuan Jatisari Melalui Penguatan Legalitas dan Efisiensi Produksi Minuman Tradisional Kunir Asem - Sujito; Mohamad Rodhi Faiz; Budi Wibowotomo; Tito Al Afrin Uwais; Fazlur Rahman Addakhi (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2026)
The community service program was carried out in collaboration with the PKK women’s group in Jatisari Village, Tajinan District, Malang Regency. The program aimed to strengthen business legality as well as improve the efficiency and quality of Kunir Asem Jatiarum production. Previously, the PKK women faced significant challenges in marketing due to the absence of production permits and distribution licenses, which limited product sales only within the village. Additionally, there was a need to enhance both product quality and production efficiency. Through this community service activity, assistance was provided to obtain essential business legality documents, including the Business Identification Number (NIB), distribution permit, BPOM registration, and halal certification. These achievements have had a significant impact, such as increasing consumer trust in Kunir Asem Jatiarum products and expanding market access. Furthermore, obtaining business legality opens opportunities for government development programs and strategic partnerships, while the halal certification adds value and competitiveness in broader markets. Ultimately, business legality serves as a fundamental foundation for the sustainability and profitability of UMKM in the modern era.